Association between Parkinson's disease and G2019S and R1441C mutations of the LRRK2 gene - LI, XIAO-XIA (Exp Ther Med, 2015)
In recent genome-wide association studies (GWAS), 11 risk loci were identified in patients with familial and sporadic Parkinson's disease (PD) in different populations. The LRRK2 gene was found to be a mutation hot spot in European and Asian populations. The aim of the present study was to investigate the incidence of G2019S and R1441C mutations in the LRRK2 gene in individuals from the Xinjiang region of China, and to explore the associations between LRRK2 gene single nucleotide mutations and susceptibility to PD in the Uyghur and Han populations of Xinjiang. A case-control study was conducted with a group of 312 patients with PD, including 130 Uyghur and 182 Han individuals. The control group comprised 359 subjects, including 179 Uyghur and 180 Han individuals. Polymerase chain reaction-restriction fragment length polymorphism and DNA sequencing methods were used to detect the G2019S and R1441C mutations in the LRRK2 gene in the Uyghur and Han populations. No known mutations or new hybrids were found. Thus, there was no evidence that Uyghur and Han patients with PD possess the G2019S or R1441C mutations of the LRRK2 gene. This does not exclude the possibility of the presence other LRRK2 gene mutations that are associated with PD in the Uyghur and Han populations. In the future, the association of the LRRK2 gene with PD development in different regions and populations requires further study, in addition to the regulatory effects of the G2019S and R1441C mutations on gene expression.